A resident‐created hospitalist curriculum for internal medicine housestaff. Issue 9 (15th April 2016) - Kumar, Andre; Smeraglio, Andrea; Witteles, Ronald; Harman, Stephanie; Nallamshetty, Shriram; Rogers, Angela; Harrington, Robert; Ahuja, Neera
Abstract : The growth of hospital medicine has led to new challenges, and recent graduates may feel unprepared to meet the expanding clinical duties expected of hospitalists. At our institution, we created a resident‐inspired hospitalist curriculum to address the training needs for the next generation of hospitalists. Our program provided 3 tiers of training: (1) clinical excellence through improved training in underemphasized areas of hospital medicine, (2) academic development through required research, quality improvement, and medical student teaching, and (3) career mentorship. In this article, we describe the genesis of our program, our final product, and the challenges of creating a curriculum while being internal medicine residents. Journal of Hospital Medicine 2016;11:646–649. © 2016 Society of Hospital Medicine